Vibration attenuation and energy harvesting in metastructures with nonlinear absorbers conserving mass and strain energy - Vasconcellos, D. P. [UNESP]; Cruz, R. S. [UNESP]; Fernandes, J. C.M. [UNESP]; Silveira, M. [UNESP] (Springer Nature, 2022)
In this work, we explore the performance of vibration attenuation and energy harvesting of a metastructure with vibration absorbers with nonlinear stiffness under harmonic excitation. We devise the metastructure with two main concepts: conservation of total mass, by designing the metastructure with the same mass as a structure without absorbers; conservation of strain energy, by designing the nonlinear absorbers with the same strain energy as a linear one. The use of metastructures for vibration attenuation and energy harvesting is attracting increasing attention from many engineering applications, as they have interesting wave filtering characteristics. The use of vibration absorbers allows band gaps in low frequencies, and nonlinear characteristics have been explored in different ways to increase the bandwidth of vibration attenuation in such metastructures. Modal analysis is used to determine eigenfrequencies, eigenmodes and frequency response (FRF) of the base structure and the metastructure with linear and nonlinear absorbers, both with five elements. The dissipated power by the absorbers’ dampers and the electric power in the piezoelectric harvester devices are analysed. The metastructure has slightly smaller attenuation at the tuned frequency while the total harvested power increases considerably near the first resonance.